Language Code Choice of Male Abdi Dalem of Karaton Ngayogyakarta Hadiningrat - Hanova Rani Eka Retnaningtyas; Mangatur Rudolf Nababan; Dwi Purnanto (Bina Nusantara University, 2019)
This research aimed to show the language code choices of male abdi dalem of Karaton Ngayogyakarta Hadiningrat because each community had its own language code choice in their daily lives, including every individual. This research was a descriptive qualitative study conducted to determine the language code choice of abdi dalem Karaton Ngayogyakarta Hadiningrat. Data were taken using questionnaires. The form of questions used was closed questions to find out the language codes choice. In addition, the open questions were used to find out the reason for selecting particular language codes. The data were in the form of an informant’s answer about the choice of a language code and the reason for the selection. This research conducted in Karaton Ngayogyakarta Hadiningrat based from UU Republik Indonesia Nomor 13 Tahun 2012 concerning the DIY Specialities. It finds that the use of Javanese Kromo dominates the language code choice used by male abdi dalem. The dominance of the use of Javanese Kromo language is considered to be the most polite language code rather than other languages presented by the researchers in the questionnaires. The next order after Javanese Kromo is Indonesian, Javanese Ngoko, Bagongan, and lastly is a foreign language.